Educational reform and popular education in Greece - Markel, Ionathan Iakov. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1986., 1986)
The evolution of an institutionalized educational system in Greece has been a turbulent one closely linked with the development of other social, economic, cultural and political institutions. This study deals with the development of Greece's educational system through reform focusing specifically on one of the most recent educational events and trends-the institutionalization and evolution of adult education known as Popular Education in Greece. Through a history of Greek educational reform reflecting broader socioeconomic and political trends, the creation of an agreeable climate or "social context" for successful progressive reform, this research examines how Popular Education commences and develops.
Keywords: Education -- Greece.; Educational change -- Greece.; Education, Greek.